One size does not fit all: Insights for engaging front‐line clinicians in pragmatic clinical trials. Issue 4 (13th October 2020) - Tambor, Ellen; Moloney, Rachael; Greene, Sarah M.
Abstract: Introduction: Despite the proliferation of pragmatic clinical trials (PCTs) conducted in health care delivery settings, we know relatively little about how practicing clinicians perceive their potential roles in such research. Empirical evidence and practical guidance concerning clinician engagement in research is needed to inform the design and successful implementation of PCTs. Methods: We conducted a two‐phase qualitative study to better understand how and to what extent practicing clinicians should be involved in PCTs and to develop guidance for researchers on engaging front‐line clinicians in PCTs. In phase one, clinicians who spend the majority of their time providing direct patient care participated in 90‐min focus groups. In phase two, we conducted key informant interviews with PCT research teams and clinicians participating in the ADAPTABLE (Aspirin Dosing: A Patient‐centric Trial Assessing Benefits and Long‐Term Effectiveness) trial. Results: Thirty‐four physicians, nurses, and other care providers from four health care delivery organizations participated in focus groups. Focus group participants stressed the importance of engaging clinicians early in the PCT planning process to identify clinically relevant study questions, provide input on study design, and customize study protocols to fit unique clinic workflows. We conducted 18 interviews with principal investigators, project managers, and clinicians involved in the ADAPTABLE trial across six clinical data research networks. Study team members described trying multiple approaches to optimize in‐clinic recruitment and enrollment of eligible patients. Successful strategies involved several key factors related to research team interactions with eligible patients, clinicians, and clinic staff. Conclusions: More active involvement by a range of clinical stakeholders in PCT planning may help researchers avoid common barriers to trial implementation. We propose a "medium‐touch" approach to involving clinicians in PCT recruitment and enrollment that focuses clinician effort where it is most critical—to reassure eligible patients that trial participation is a safe alternative for them.